EFEKTIVITAS DAUN PISANG MANURU SEBAGAI BAHAN PENGAWET ALAMI DALAM PENGOLAHAN SAMBAL IKAN TERI KEMASAN - Wa Ode Nafilawati; Mariani L Mariani; Ilian Elvira; Rahayu Endah Purwanti (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Fish-based sambal products are considered ready-to-eat foods that are highly susceptible to microbial spoilage during storage, thereby requiring safe and natural preservation strategies. One promising solution is the use of manuru banana leaf extract (MBLE), which contains active antimicrobial and antioxidant compounds. This study aimed to examine the effect of MBLE addition on the quality and shelf life of anchovy sambal under accelerated storage conditions. The extract was obtained via ethanol maceration of dried banana leaves and applied to the sambal at concentrations of 0% (control), 2%, 3%, and 4%. Samples were stored at 55 °C for 21 days. Parameters evaluated included pH, total plate count (TPC), and organoleptic attributes such as color, characteristic sambal aroma, off-odor intensity, and texture. Results revealed that MBLE addition had no significant effect on pH reduction but effectively inhibited microbial growth, with the best performance at 4% MBLE, which yielded the lowest microbial count (2.6 × 10⁵ CFU/g). Organoleptic assessment indicated that sambal with 2% MBLE received the highest preference scores in terms of color, aroma, and overall sensory acceptance. Noticeable sensory quality degradation was observed from day 7 of storage. It can be concluded that MBLE is effective in extending the shelf life of anchovy sambal and serves as a promising natural preservative at concentrations between 2% and 4%. Further research is recommended to explore the interaction of packaging methods and storage temperatures on the product’s physicochemical and sensory stability throughout its distribution chain.